Hearts and Minds: Real-Life Cardiotoxicity With Clozapine in Psychosis. Issue 6 (December 2017) - Joy, George; Whiskey, Eromona; Bolstridge, Mark; Porras-Segovia, Alejandro; McDonagh, Theresa A.; Plymen, Carla M.; Shergill, Sukhi S.
Abstract: Background: Schizophrenia has a 1% prevalence in the population; 30% of these patients are treatment refractory. Clozapine is the only drug licensed to treat treatment refractory psychosis, but concerns about potential adverse effects result in only a proportion of eligible patients being treated. Although a well-documented neutropenia risk is mitigated by routine blood testing, cardiac toxicity is a commonly cited reason to discontinue clozapine treatment. However, there is little data on the real-life cardiac outcomes in those receiving clozapine treatment. Methods: Retrospective review of electrocardiogram, echocardiogram, and clinical outcomes in 39 inpatients with treatment-refractory schizophrenia, treated with clozapine and other antipsychotic medication, referred for cardiology opinion. Results: Commonest reasons for referral were development of left ventricular (LV) impairment or sinus tachycardia with normal LV function. Patients were reviewed by a range of cardiologists, receiving varied interventions. Median LV ejection fraction in the clozapine group was normal (52%). Serial echocardiograms demonstrated that clozapine-treated patients with LV impairment had no change in LV ejection fraction over a 4-month follow-up. Left ventricular ejection fraction did not differ between patients treated with clozapine and other antipsychotics. However, over an 11-year follow-up period, 48% of patients had discontinued clozapine treatment. Conclusions: This naturalistic study demonstrates that clozapine is not associated with significant cardiac mortality or morbidity. There is a real need for multidisciplinary working between specialist cardiologists and psychiatrists caring for these complex patients to facilitate optimal long-term physical and mental health outcomes.